Dynamics and Impacts of the May 8th, 1902 Pyroclastic Current at Mount Pelée (Martinique): New Insights From Numerical Modeling - Gueugneau, Valentin; Kelfoun, Karim; Charbonnier, Sylvain; Germa, Aurelie; Carazzo, Guillaume (Frontiers in Earth Science, 2020)
The Mount Pelée May 8th, 1902 eruption is responsible for the deaths of more than 29,000 people, as well as the nearly-complete destruction of the city of Saint Pierre by a single pyroclastic current, and is, sadly, the deadliest eruption of the 20th century. Despite intensive field studies on the associated deposits, the eruptive sequence as well as the generation of the pyroclastic current and its internal dynamics are still debated. This study takes a different approach by developing numerical simulations of the May 8, 1902 pyroclastic current event using the two-phase version of VolcFlow to model both the concentrated part (also called block-and-ash flow) and the dilute part (also called ash-cloud surge). The scenario for the simulation consists of an ash-cloud surge generated from a block-and-ash flow initially supplied from the artificially recreated 1902 crater. Physical flow parameters are either extracted from field data or estimated empirically when no value is found in the literature. The simulated pyroclastic current rapidly overflows from the southern V-shaped crater outlet. The concentrated part stays confined in the Rivière Blanche, whereas the dilute part expands radially and spreads westward, seaward, and eastward, ultimately reaching St Pierre, 8 km away, within 330 s. The extent of both parts of the simulated current, as well as the thickness and the direction of the ash-cloud surge with a total volume of 32 ×106 m3, for which a significant part (one third) is deposited in the sea (not recorded in previous studies), is accurately reproduced. The pear-like shape of the ash-cloud surge deposit is explained by a late surge production along the Rivière Blanche. Simulations demonstrate that a blast-like event is not mandatory for this eruption, and that most of the key flow dynamics (flow direction, extent, thickness of the deposit) can be accurately simulated with such a simplified two-phase, depth-averaged modelling approach. Results also highlight the key role played by the topography in controlling transport and deposition mechanisms of such pyroclastic currents especially the lateral spreading of the ash-cloud surge.